2022
DOI: 10.3390/children9050620
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Children with Acute Appendicitis

Abstract: We hypothesized that—as in other common pediatric conditions—acute appendicitis (AA) could be complicated by acute kidney injury (AKI). We aimed to investigate the prevalence of, and the factors associated with AKI in a cohort of patients with AA. We retrospectively collected data of 122 children (63.9% of male gender; mean age 8.6 ± 2.9 years; range: 2.2–13.9 years) hospitalized for AA. AKI was defined according to the Kidney Disease/Improving Global Outcomes creatinine criteria. We considered a basal serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…During the hospitalization, none of our patients was diagnosed with AKI. This, in addition to the presence of only one report describing an association between AKI and bronchiolitis [ 8 ], further confirms our meaning that AKI, especially in its milder forms, is often under-recognized in children [ 4 7 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…During the hospitalization, none of our patients was diagnosed with AKI. This, in addition to the presence of only one report describing an association between AKI and bronchiolitis [ 8 ], further confirms our meaning that AKI, especially in its milder forms, is often under-recognized in children [ 4 7 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our study group previously analyzed both prevalence of and factors associated with AKI in different groups of children [ 4 7 ]. In children with acute gastroenteritis, we found lower birth weight and higher hematocrit levels in patients who developed AKI compared with those who did not [ 6 ], while in children with community-acquired pneumonia, we found lower birth weight and higher percentage of preterm birth in patients developing AKI compared with those who did not [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the prevalence of AKI in malaria against other diseases, the prevalence of AKI reported in this study was comparable with the one reported by Marzuillo et al [ 13 ] among children with diabetes mellitus (43.8%). However, it was significantly higher than in acute gastroenteritis (24.6%), community acquired pneumonia (20.4%), and acute appendicitis (7.4%) [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Acute kidney injury (AKI) is common but often undiagnosed, in several paediatric diseases. [8][9][10][11][12] Studies have shown that 12-52% of adult patients hospitalised with fUTI develop AKI. [13][14][15] However, no studies are available in children, with only sporadic cases reporting AKI during paediatric fUTI.…”
Section: Introductionmentioning
confidence: 99%